Bottom-Up Synthesis and Sensor Applications of Biomimetic Nanostructures - Wang, Li (Materials (Basel), 2016)
The combination of nanotechnology, biology, and bioengineering greatly improved the developments of nanomaterials with unique functions and properties. Biomolecules as the nanoscale building blocks play very important roles for the final formation of functional nanostructures. Many kinds of novel nanostructures have been created by using the bioinspired self-assembly and subsequent binding with various nanoparticles. In this review, we summarized the studies on the fabrications and sensor applications of biomimetic nanostructures. The strategies for creating different bottom-up nanostructures by using biomolecules like DNA, protein, peptide, and virus, as well as microorganisms like bacteria and plant leaf are introduced. In addition, the potential applications of the synthesized biomimetic nanostructures for colorimetry, fluorescence, surface plasmon resonance, surface-enhanced Raman scattering, electrical resistance, electrochemistry, and quartz crystal microbalance sensors are presented. This review will promote the understanding of relationships between biomolecules/microorganisms and functional nanomaterials in one way, and in another way it will guide the design and synthesis of biomimetic nanomaterials with unique properties in the future.